Quality assessment of vocational school libraries using the WebQual 4.0 technique - Setya Raharja; Rahmat Fadhli; Meilina Bustari; Widia Murni Wijaya (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. The purpose of this study is to assess the quality of the vocational school library websites and to determine the factors that influence the websites’ quality. Data Collection Methods. This paper used a quantitative method with a population of vocational high school students in Yogyakarta. A questionnaire was used to collect data from 357 students from three schools. Data Analysis. WebQual Index (WQI) and Importance Performance Analysis (IPA) data analysis approaches were used. Results and Discussion. This study discovered a WQI score of 0.87 on the library website of SMKN 1 Bantul, 0.85 on the library website of SMKN 1 Godean, and 0.81 on the library website of SMKN 2 Yogyakarta. According to user views, the quality of the library website of SMKN 1 Bantul is high. The result showed that users considered six factors, these were positive website experience, reliable information offered by the website, personal data security, personalization features, ease of communication with the website manager, and website manager information. Conclusion. In general, the quality of the Yogyakarta vocational high school library website is good in three areas: usability, information quality, and interaction service quality.